Experimental and numerical investigation of progressive damage and failure behavior for 2.5D woven alumina fiber/silica matrix composites under a complex in-plane stress state. (15th August 2021) - Deng, Linlin; Hao, Ziqing; Zhang, Lei; Liu, Liu
Highlights: The linear on-axis tensile response with a brittle fracture is governed by the axial fiber bundle. The tensile response with reduced ultimate stress results from multiple damages in axial and transverse fiber bundles. The damage acceleration under a biaxial tension and shear is quantified using a shear contribution coefficient. The thickness effect on the tensile strength is quantified under a biaxial tension and shear. Abstract: The focus of this work is to characterize the progressive damage and failure behavior of 2.5D woven alumina fiber reinforced silica ceramic matrix thin composite specimen under a planar tension-shear stress state. The tensile and shear stress–strain diagrams in the principal material coordinate system were obtained using the off-axis tension test with the digital image correlation technique. A mesoscale finite element model of the composite material was developed within the framework of continuum damage mechanics. The thickness effect on the macroscopic mechanical response was considered by removing the periodic boundary conditions along the thickness direction. The macroscopic stress–strain response given by the numerical model was validated by the experimental results. The interaction of the planar biaxial tension and shear stresses was taken into account in the model, quantified using a shear contribution coefficient in the modified 3D Hashin failure criterion. The results from the damage evolution analysis indicate that the linear tensile stress–strain response with a brittle fracture characteristic for the on-axis tension specimen is governed by the axial fiber bundle. The nonlinear tensile stress–strain response with the significantly reduced ultimate stress under biaxial tension and shear stress state results from multiple damages with evolution in both axial and transverse fiber bundles. Both the effective tensile modulus and the ultimate tensile strength increase with increasing the thickness of the specimen due to the increase of the fiber volume fraction. The strengthening induced by the size effect is less significant for the specimen under biaxial tension and shear stress state than that for the on-axis tension specimen owing to the involvement of shear response dominated by the matrix of the material. The results of this study provide new insight into the failure of 2.5D woven ceramic-based composite material, which contributes to the optimal design of the reusable thermal protection system structure.